Analysis of Difference between the Objective Effect and Subjective Effect in Rehabilitation Treatment of Dysphagia after Stroke - Shaohong XU; Shan TIAN; Ruiping HU; Junfa WU; Congyu JIANG; Dandan LI; Kewei YU; Yi WU (康复学报)
Objective:To analyze the reason of the difference of clinical curative effect after rehabilitation treatment for stroke patients with dysphagia.Methods:A total of thirty stroke patients with dysphagia were evaluated with standardized swallowing assessment (SSA), video fluoroscopic swallowing study (VFSS) and swallowing disorder patient's quality of life scale (SWAL-QOL).Results:After four weeks of rehabilitation treatment, the SSA, VFSS and SWAL-QOL scores were significantly increased (P<0.01), and the SWAL-QOL score was lower than the SSA or VFSS score, but there was not a significant difference among them.Conclusion:A reason for the differences of SSA, VFSS and SWAL-QOL is the objectivity and subjectivity of curative evaluation. SWAL-QOL score is focus on the subjective effect and lower, suggesting that for patients with dysphagia, the psychological burden of swallowing disorder has a significant impact on the clinical outcome of patients.